Fatigue crack propagation analysis in 2024-T351 aluminium alloy using nonlinear parameters. (December 2021) - Borges, M.F.; Lopez-Crespo, P.; Antunes, F.V.; Moreno, B.; Prates, P.; Camas, D.; Neto, D.M.
Highlights: Novel fatigue crack growth (FCG) study of 2024-T351 aluminium alloy based on plasticity developed at the crack tip. Combines experimental FCG data with powerful numerical model replicating the material properties, geometry and loading conditions. Determination of crack closure level based on contact of the first node behind the crack tip. Establishing a new nearly linear relation between da/dN and plastic component of the CTOD. Abstract: In this work, fatigue crack growth (FCG) in the 2024-T351 aluminium alloy is studied using the plastic CTOD range, Δ δp . Experimental tests were performed on 12 mm thick CT specimens in order to obtain FCG rate and in cylindrical specimens to obtain stress–strain loops. A numerical analysis replicated the experimental work in terms of material, geometry and loading conditions, but assuming pure plane strain state, in order to obtain Δ δp . The material parameters were fitted using the experimental stress–strain loops. The experimental work showed an increase of FCG rate with the increase of stress ratio from R  = 0.1 to R  = 0.7 mm, which indicated the existence of the crack closure phenomenon. However, the analysis of the position of the first node behind the crack tip showed that there is no crack closure under plane strain state, while a maximum value of 36% was found for plane stress state. Therefore, the surfaces influence FCG rate even in 12 mm thick specimens. A nearly linear relation was found between da/dN and Δ δp . The comparison with other aluminium alloys showed that there is a significant influence of material on da/dN -Δ δp relation. The change from plane strain to plane stress state decreased FCG rate due to crack closure. Under plane strain state there is a minor influence of stress ratio in the range R  = 0.1–0.7, also because there is no crack closure. Finally, a comparison was made between plastic CTOD and cumulative plastic strain at the crack tip. Well defined relations were found, showing that both parameters can be used to quantify crack tip deformation.